2020
DOI: 10.1080/22221751.2020.1810134
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Enterococcus isolates in postoperative endophthalmitis by selection pressure of fluoroquinolones: an 11-year multicenter and experimental study

Abstract: Postoperative endophthalmitis (PE) is the devastating complication that frequently results in vision loss. Recently, enterococcus have emerged as a major cause of PE in several countries and resulted in poor visual outcome. However, the reason remains elusive. We investigate whether selection pressure of fluoroquinolone exerts effects on microorganism profiles isolated from PE. Medical records of patients who were diagnosed with PE at eight resident training institutions between January 2004 and December 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The incidence of enterococcal endophthalmitis after cataract surgery tends to increase recently. Enterococci are more resistant to the fourth-generation fluoroquinolones than coagulase-negative Staphylococci [ 26 , 42 ]. Aminoglycoside inactivating enzyme encoded by the aac(6’)-aph(2’’) gene can confer resistance to high concentrations of gentamicin [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of enterococcal endophthalmitis after cataract surgery tends to increase recently. Enterococci are more resistant to the fourth-generation fluoroquinolones than coagulase-negative Staphylococci [ 26 , 42 ]. Aminoglycoside inactivating enzyme encoded by the aac(6’)-aph(2’’) gene can confer resistance to high concentrations of gentamicin [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the most prevalent bacteria in the conjunctiva are CNS, including S. epidermidis , they have been the major causative agent of PE after surgery. On the other hand, several recent reports on PE in Korea, Sweden, and Taiwan indicated that E. faecalis has become the top causative agent of PE ( 6 , 9 11 ). Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the distribution of the causative bacteria of postoperative PE changed in Korea, Sweden, and Taiwan ( 9 11 ). These changes may reflect alterations of conjunctival microflora in the PE patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterococci are important pathogens causing hospital-and community-acquired abdominal infections, with Enterococcus faecalis and Enterococcus faecium accounting for most enterococcal infections in humans, including urinary tract infections, surgical site infections, bacteremia, endocarditis and tissue damage [1,2]. Enterococcus species are of clinical importance because they lead to a fulminant and destructive disease course [3]. A recent report showed that Enterococcus accounted for 20% of bloodstream infections in China, with a mortality rate of 24% [4].…”
Section: Introductionmentioning
confidence: 99%